Steroid hormone response to running and circuit training exercise in trained men utilising ELISA and mass spectrometry - Tanner, A. V.; Nielsen, B. V.; Allgrove, J. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
However, it is unclear how different forms of training affect the response of these hormones. Additionally mass spectrometry (MS) is currently widely used in pharmaceutical and health industries to measure small biomarkers; however use in sports research is limited. The purpose of this study was to examine the effect of various training sessions on salivary and plasma C and T in male runners and test the validity of MS to measure salivary stress hormones in exercise research. Methods: 10 male runners completed the study. Four trials were completed: a) 30 min tempo run at lactate threshold (TEMP); b) 30 mins running alternating 3.5 mins at 90% and 2 mins at 30% VO2max (INT); c) 30 mins circuit training with 3x10 exercises of 30 secs with 30 secs recovery between exercises (CIR) and d) 30 mins rest (REST). Saliva and plasma samples were collected pre exercise and at 0, 15, 30 and 60 mins post exercise and rating of perceived exertion (RPE) and heart rate (HR) were recorded. Plasma and saliva samples were analysed for C and T with ELISA and saliva samples also with MS. Results: Mean HR (±SD) was: 161 ± 7, 159 ± 14, 130 ± 12 and 63 ± 1 beats per minute for TEMP, INT, CIR and REST respectively with INT and TEMP higher than REST. Peak HR was higher in INT compared to CIR (p=0.021) and TEMP (p=0.004). Salivary C was higher in INT than REST (p=0.004) and remained elevated at 60 mins post exercise. Salivary T was higher than REST immediately post exercise in INT, TEMP and CIR (p<0.05). Overall, TEMP was higher than REST (p=0.05). Plasma and salivary measures were correlated in C (r=0.813) and T (r=0.568) with peaks occurring simultaneously. There was a strong correlation for salivary C measured with MS and ELISA (r=0.934, p<0.05). Discussion: This study found that an INT session elicited an increase in salivary C which is in agreement with previous research (Vuorimaa et al., 2008; Hough et al., 2011). The study implied peak HR may indicate salivary C levels and could be a useful tool to assess training stress. Moreover, MS was revealed as a valid technique to measure the salivary C response to exercise and routine use in the exercise arena pursued. Further method development is required to reliably measure T with MS due to low assay sensitivity; however MS remains the gold standard in hospital and pharmaceutical analysis.